On the impingement of droplets upon moving films - Mitchell, Antony James (2019)
Environmental and economic considerations are amongst the key challenges faced in the contemporary aviation industry. Increasing fuel, labour and parts prices, coupled with an ever-tightening legislative environment necessitate a programme of continuing improvement to engine design.